Does thinking style affect the impacts of satisfaction and reputation on repurchase intention? A cross-national comparison - Öznur Özkan Tektaş; Canan Eryigit; Ozge Tayfur Ekmekci (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2017)
The purpose of this study is to test whether the influence of satisfaction and reputation on repurchase intention varies among analytic and holistic thinkers. We employed an individual level approach to measure cross-cultural differences regarding thinking style and other variables. We made a cross-cultural comparison via analyzing the effects of satisfaction and firm reputation on repurchase intention, using data from the USA and Turkey that reflect analytic and holistic thinking cultures, respectively. Also, we conducted intra-cultural analyses in which the USA data and Turkish data were analyzed separately. Findings from these analyses revealed that holistic and analytic thinking styles create differences at the individual level (intra-cultural) but not at the cultural level (cross-cultural). In the Turkish sample, the impact of reputation on repurchase intention is found to be stronger than that of satisfaction for holistic thinkers.
Keywords: M3; M31; 650; holistic thinking; analytic thinking; customer satisfaction; firm reputation; repurchase intention